2017
DOI: 10.1080/00131911.2017.1363718
|View full text |Cite
|
Sign up to set email alerts
|

Let me entertain you: the ambivalent role of university lecturers as educators and performers

Abstract: In England, higher education is more marketised than ever before as the difference between students and consumers is increasingly blurred, propelled by the rise in tuition fees. With students demanding more for their money, the role of university lecturers continues to change. This study explores the ways in which lecturers re-evaluate and reconstruct their roles and responsibilities in light of heightened student expectations. We draw on 30 in-depth interviews with lecturers from the social sciences, across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…By uncovering some of these ideal characteristics, students would be better informed and will have the opportunity to develop these attributes of the ideal university student, if desired, which could alleviate the mismatch of values and expectations and potentially strengthen the lecturer-student relationshipa key influence in students' academic progress and outcome (Chetty, Friedman, and Rockoff 2014;Rockoff 2004). Hence, the concept of 'ideal' university student has the potential to bridge differences and manage expectations between lecturers and students, which have been stretched due to consumerism and greater student demands (Brown and Carasso 2013;Wong and Chiu 2019a). We believe in the need for greater openness on the expectations and ideals of students at university.…”
Section: Understanding Idealsmentioning
confidence: 99%
“…By uncovering some of these ideal characteristics, students would be better informed and will have the opportunity to develop these attributes of the ideal university student, if desired, which could alleviate the mismatch of values and expectations and potentially strengthen the lecturer-student relationshipa key influence in students' academic progress and outcome (Chetty, Friedman, and Rockoff 2014;Rockoff 2004). Hence, the concept of 'ideal' university student has the potential to bridge differences and manage expectations between lecturers and students, which have been stretched due to consumerism and greater student demands (Brown and Carasso 2013;Wong and Chiu 2019a). We believe in the need for greater openness on the expectations and ideals of students at university.…”
Section: Understanding Idealsmentioning
confidence: 99%
“…If students are framed as customers of HE, then the learning process might be compromised, because they may not know what they want [17,50], they are less likely to be involved in their education [61,65], they may see themselves as customers who are purchasing academic services in order to obtain a degree [66], they could see the university as a passport for a "better job" rather than a learning experience [62], seek to "have" a degree instead of learning the professional skills [39], may feel "entitled to a degree" [67], think they have the right to judge the "goodness" of a teacher [68], think they have equivalent rights as in the everyday marketplace [19], and may demand entertaining lessons [69]. Since the term 'customer' may have different interpretations according to the context of the experience, this may not be the proper manner in which to designate students in HE settings.…”
Section: Controversies Of the Student-as-customer Metaphormentioning
confidence: 99%
“…However, realising this purpose does not just happen. Research has shown that it is determined by various factors at the heart of which is lecturers' job performance (Wong & Yuan-Li, 2019). Lecturers' job performance refers to the extent to which lecturers complete the teaching, research and community service tasks, responsibilities and activities intended to facilitate student learning and achievement of desired educational outcomes (Alfagira et al, 2017;Onoyase, 2017;Victor & Babatunde, 2014;Naseer, 2010).…”
Section: Introductionmentioning
confidence: 99%